Belonging in our belongings - Ng, Teri Shun Yi (Nanyang Technological University, 2021)
Belonging in Our Belongings examines a redefinition of home through a personal narrative and investigates the details of our belongings; the mundane around us that is often overlooked. Drawing from the ever so familiar space and definition of home, this project looks at how human beings situate themselves in a home, or perhaps, many different homes throughout one’s lifetime. Although typically portraying a safe space, every individual’s definition of home varies from one another. This space often encapsulates objects such as personal keepsakes, and these objects have a story to tell. Grasping onto the concept of nostalgia and emotional attachment to objects, this project provides me with an opportunity to share my story as a third culture kid and explore the relationship between objects, identity, and creating a sense of home in a place away from home - to make up for the lack of a permanent space to call home. The definition of home is reinvented to convey a feeling of comfort towards a pre-existing space that is linked to items which bring forth a distant memory. Belonging in Our Belongings presents itself as a series of visual explorations, representing previous spaces through objects which were present in that past time.